2017
DOI: 10.1101/169524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppression of Transposable Elements in Leukemic Stem Cells

Abstract: 28Genomic transposable elements (TEs) comprise nearly half of the human genome.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 49 publications
(35 reference statements)
3
19
0
Order By: Relevance
“…ALUJo, MER11A, LTR14A and others) that were recently described as being prognostic biomarkers in TCGA AML patient samples and where expression of LTR14A, LTR45B, MER77 and Tigger9b are hazardous covariates that correlate with increased AML risk (Colombo et al, 2018). The distinct repeat subtypes identi ed in our study and in Colombo et al, (2017;Colombo et al, 2018) appear to be the most susceptible repeat elements that are found to have altered expression in AML.…”
Section: Expression Analysis Of Distinct Repeat Elements In Amlsupporting
confidence: 64%
See 3 more Smart Citations
“…ALUJo, MER11A, LTR14A and others) that were recently described as being prognostic biomarkers in TCGA AML patient samples and where expression of LTR14A, LTR45B, MER77 and Tigger9b are hazardous covariates that correlate with increased AML risk (Colombo et al, 2018). The distinct repeat subtypes identi ed in our study and in Colombo et al, (2017;Colombo et al, 2018) appear to be the most susceptible repeat elements that are found to have altered expression in AML.…”
Section: Expression Analysis Of Distinct Repeat Elements In Amlsupporting
confidence: 64%
“…Collectively, these insights demonstrate separate functions for the dysregulation of distinct repeat subclasses in either the progression or attenuation of human solid tumors. For hematopoietic malignancies, such as AML, only very few studies on the expression/dysregulation of repeat elements were done (Colombo et al, 2017;Colombo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, evidence suggests that TEs mediated activation of innate immune response facilitate clearance of cancer cells [19,20]. More directly, we recently showed that leukemic stem cells have repressed expression of TEs along with immune pathways [39], indicative of a survival mechanism to evade an innate immune response. Identification and targeting of similar oncogenic-addictions could prove essential therapeutic strategies, as recently shown [40].…”
Section: Discussionmentioning
confidence: 85%